FAKTOR YANG BERHUBUNGAN DENGAN RUPTURE PERINEUM PADA PERSALINAN NORMAL - Dwi Saputri Susita Utami; Eka Juniarty (WOMB Midwifery Journal, 2022)
Perineal rupture is one of the causes of cases of obstetric bleeding which will increase in 2021 with a prevalence of 17.6% in RSUD Kota Prabumulih. The purpose of this study was to determine the factors associated with perineal rupture in normal delivery. The research method is analytic-observational using a cross-sectional approach at the RSUD Kota Prabumulih. The population of this study was 1778 mothers giving birth from January to May 2022 and based on the sample calculation formula, it was found that 326 mothers who were in labor as research samples were taken by simple random sampling. Data collection was carried out using secondary data, namely the medical records of the RSUD Kota Prabumulih and the instrument used was a checklist. Data analysis used SPSS with chi-square statistical test and 95% confidence level. The results of this study were 44.8% (146) of birth mothers experienced perineal rupture. Age, gestation interval, and birth weight were related to the incidence of perineal rupture (p<0.000, p<0.000, and p<0.000) respectively. The conclusion of this study is the need for attention and awareness of midwives and mothers with conditions of age <20 years and >35 years, gestational interval ≤2 years, and estimated fetal weight ≥4000 grams during pregnancy for the incidence of perineal rupture.